Comparative analysis of medical tourism in the region and modelling international medical tourism demand: in the case of Malaysia - Ong, Yean Xin (2020)
The international medical tourism market was forecast to be worth US$208 billion by year 2027. This lucrative industry not only attracts foreign currencies; it fuels the developments of healthcare and tourism sectors and spurs national economic developments. This research had two overarching objectives. First, this paper aimed to identify, compare and contrast the strengths, weaknesses, opportunities, and threats (SWOT) of four medical tourism rivals in the region, namely Malaysia, Thailand, India and Singapore and identify the competitive strengths of the medical destinations in the region. Second, this study proposed a model to examine the relationship between economic and socio-demographic variables and the inbound medical tourism demand of Malaysia. The study adopted fixed effects model to estimate the model equation. The findings of the study indicated that the destination prices could significantly influence the inbound medical tourism demand of Malaysia. Furthermore, SWOT analysis was undertaken to facilitate a comprehensive view of the medical destinations in the region and identify the nations’ respective competitive advantages in an effort to deliver practical and pertinent recommendations to the domestic medical tourism practitioners and policymakers to strengthen the sector in question.